2003
DOI: 10.1128/cdli.10.6.1153-1156.2003
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic Expression and Antigenic Characterization of Three RecombinantLeishmaniaAntigens for Serological Diagnosis of Canine Leishmaniasis

Abstract: Leishmaniases comprise a broad spectrum of human and animal diseases caused by infection of the mononuclear phagocyte system with protozoan parasites of the genus Leishmania. These agents are transmitted by the bite of phlebotomine sandflies in tropical, subtropical, and temperate zones of the world. Although humans are the sole reservoir hosts for some Leishmania species, in most cases other animals play a major role in the maintenance of infections. In countries of the Mediterranean basin, Middle East, and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 12 publications
3
31
2
Order By: Relevance
“…The difference in sensitivity might be that a quantitative method was used in the current study whereas the rK26 strip test used in the other study is a qualitative method of antibody detection. Other studies conducted in symptomatic canine VL cases in Brazil showed higher sensitivity by ELISA using rK9 and rK26 antigen [20][21][22]. The lower sensitivity in this study may be due to the fact that dog is a different species than human.…”
Section: Discussioncontrasting
confidence: 51%
“…The difference in sensitivity might be that a quantitative method was used in the current study whereas the rK26 strip test used in the other study is a qualitative method of antibody detection. Other studies conducted in symptomatic canine VL cases in Brazil showed higher sensitivity by ELISA using rK9 and rK26 antigen [20][21][22]. The lower sensitivity in this study may be due to the fact that dog is a different species than human.…”
Section: Discussioncontrasting
confidence: 51%
“…Two recombinant plasmids containing, respectively, the whole open reading frame of K9 antigen (GenBank accession number AF131227) and the K39sub (GenBank accession number L07879) have been developed previously (34) and served as PCR templates in this study.…”
Section: Figmentioning
confidence: 99%
“…The three recombinant antigens showed independent and complementary immunoreactivities and reached an excellent agreement with IFAT when used in parallel (34). An ideal test would therefore employ a combination of relevant epitopes in a single recombinant antigen, more specific than crude antigen preparation and more sensitive than single epitope-based ELISA.…”
mentioning
confidence: 99%
“…HSP70 is a target for the humoral response during human leishmaniasis (13) and has been shown to stimulate the murine immune system (23). rK39 is mainly expressed in the amastigote stage and elicits a strong immune response in both asymptomatic and clinically infected dogs (26).…”
mentioning
confidence: 99%